2008
DOI: 10.1016/j.otohns.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the sphenoid sinus on the CT using multiplanar reconstruction technique

Abstract: OBJECTIVE: To clarify the three-dimensional anatomical features of the sphenoid sinus and its surrounding structures as are relevant to performing an endoscopic sphenoidotomy. METHODS: Various dimensions of 224 CT images of the sphenoid sinus and surrounding structures from 122 Japanese adult patients were measured using the multiplanar reconstruction technique. RESULTS: The mean distance from the nasal sill to the sphenoid ostium was nearly 66 mm, and that from the sphenoid ostium to the posterior wall of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 9 publications
(20 reference statements)
3
22
0
2
Order By: Relevance
“…This trend was particularly apparent when comparing the distances from BOC to SF and to AS. Table 3 shows the mean distances be- BOC and AS was similar to previous studies measuring the distance between the nasal sill and ostium of the sphenoid sinus, although the anatomical points for measurement were different 5,12) . The mean distance between the BOC and AS is more applicable to a transseptal approach than an endonasal approach.…”
Section: Changes Of the Measurements With Degree Of Pneumatization Ansupporting
confidence: 77%
“…This trend was particularly apparent when comparing the distances from BOC to SF and to AS. Table 3 shows the mean distances be- BOC and AS was similar to previous studies measuring the distance between the nasal sill and ostium of the sphenoid sinus, although the anatomical points for measurement were different 5,12) . The mean distance between the BOC and AS is more applicable to a transseptal approach than an endonasal approach.…”
Section: Changes Of the Measurements With Degree Of Pneumatization Ansupporting
confidence: 77%
“…With this technique, any arbitrarily reconstructed image desired can be obtained by changing the angle of the plane and by changing the target location. We previously reported new findings that we obtained regarding the spatial anatomy and dimensions of the eustachian tube and sphenoid sinus by using these techniques (7,8). This is why we applied these techniques to clarify the pathogenesis of the vertigo of the present case by analyzing the spatial relationship among the tumor, nerves, and vessels.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, as digital imaging and communications in medicine (DICOM) of computed tomography (CT) and MRI, and viewing and processing software have advanced (6), it has become possible to observe and measure structures seen in the CT and MRI three-dimensionally in a way that meets our needs (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they found that both openings were situated halfway between the superior and inferior margin of the sphenoid sinus anterior wall. Similar to Lang, Enatsu et al propounded that both SOs were located almost halfway on the anterior aspect of the sphenoid bone vertically; they also alleged that the spatial orientation of both relative to the carotid artery and the optic nerve showed no remarkable variation in their study (9,13). They resolved, however, that vertical and horizontal data of each SO varied significantly (9).…”
Section: Locationmentioning
confidence: 95%